Did God Cause the World by an Act of Free Will, According to Aristotle? A Reading Based on Thomistic Insights - Carlos A. Casanova (Religions)
As a contribution to the reflection on whether classic Greek philosophy gave priority either to Necessity and the Fatum or to freedom, this paper endeavors to prove three theses: (1) according to Aristotle, God caused the being of the world by an act of His will; (2) such an act of divine will was free and not necessary; (3) however, such causation is subject to the necessity of supposition. In order to do this, the paper delves into the interpretation of many passages contained in the Physics, the Metaphysics, De anima, Nicomachean Ethics, Eudemian Ethics as well as Politics, Topika, De generatione et corruptione, De coelo and De partibus animalium. This interpretation benefits from Aquinas’ acute analysis. In such passages, Aristotle holds that (1) God’s causal power must be exercised not in proportion to the magnitude of divine power, but to the requirements of the effect; (2) such a way of acting is similar to human power; (3) nature is subject to teleology because it is caused by an intellectual power; (4) God is the highest intelligible and the highest good, totally autarchic; and (5) just as the highest intelligible is simultaneously also intellect, so too is the highest good simultaneously also will.